Screening of Auditory Processing Disorders in School-Aged Children in Tehran, Iran Using the Auditory Processing Domain Questionnaire. - Jarollahi, Famoush; Pourbakht, Akram; Jalaie, Shohreh; Oruie, Mahbobeh (Auditory & Vestibular Research (2423-480X), 2022)
Background and Aim: Early detection of auditory processing disorders (APD) is essential for preventing learning and educational problems in school-aged children. It is crucial to take into account the comorbidity with APD, as well. The goal of APD screening is to obtain the basic information about those with auditory disorders to be referred for further evaluation. This study aimed to identify the elementary school students at risk of APD in Tehran, Iran. Methods: Participants were the parents of 536 children selected from 11 elementary schools in four districts of Tehran city. The schools in each district were selected by a random clustering method. The auditory system of students was first evaluated. The parents were then asked to complete the Persian version of the auditory processing domain questionnaire (APDQ). Results: The prevalence of APD was 3.3% in girls and 8.3% in boys and the difference between them was statistically significant (p=0.021). The overall prevalence of APD was 4.6% based on the cut-off points of four APDQ domains, with a male-to-female ratio of 2.6. Conclusion: It is necessary to screen APD in school-aged children to minimize learning and educational problems in them. Moreover, there is a need for developing screening methods to provide timely detection and appropriate intervention for those at risk of APD.